Exploring Social Complexity: Continuum Theory and a Research Design Model for Archival Research - Gibbons, Leisa (Monash University Publishing, 2017)
Over the past 25 years, archival science as a field has grown in volume, sophistication, and construction. Of particular interest are trends in archival research focusing on communities and their archival needs, as well as the broader social issues that impact these communities. How might a researcher conceptualise and account for their position within the research project? How might the researcher design the project in a way that balances the needs and interests of communities and those of the researcher? In response to such questions, this essay describes a model for reflexive research design based on continuum theory. Utilising a case study exploring the social media platform YouTube, this essay presents a research design model that emphasises continual and iterative reflection on the part of the researcher before, during, and after the processes of research. The purpose of the model is to provide the researcher with a tool for construction, to help design the plan, approach and goals of a research project, to draw out potential research methods, methodologies, tools and community knowledge through an interwoven and non-linear development process. The model addresses complexity in developing research projects across disciplines and stakeholders by providing a means to understand or “see” the mix of contexts brought to and created as a result of research. The model is an outcome of the YouTube case study research I performed, but is also part of it as working with it played a significant role shaping the research as an ongoing process.